2020
DOI: 10.4251/wjgo.v12.i10.1133
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive vs open pancreatectomy for nonfunctioning pancreatic neuroendocrine tumors

Abstract: BACKGROUND The mainstay of treating nonfunctioning-pancreatic neuroendocrine tumors(NF-PNETs) is surgical resection. However, minimally invasive approaches to pancreatic resection for treating NF-PNETs are not widely accepted, and the long-term oncological outcomes of such approaches remain unknown. AIM To determine the short- and long-term outcomes of minimally invasive pancreatic resection conducted in patients with NF-PNETs. METHODS Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Another study by Kim and colleagues focusing on NF-PNETs found that MIS approaches yielded comparable disease-free and overall survival to open approaches, with shorter hospital stays despite longer operative duration in the MIS group. Furthermore, lymph node yield was similar between the approaches [61]. Sutton and colleagues recently corroborated these findings in a multi-institutional registry involving 282 patients [62].…”
Section: Open Versus Minimally Invasive Resectionmentioning
confidence: 65%
“…Another study by Kim and colleagues focusing on NF-PNETs found that MIS approaches yielded comparable disease-free and overall survival to open approaches, with shorter hospital stays despite longer operative duration in the MIS group. Furthermore, lymph node yield was similar between the approaches [61]. Sutton and colleagues recently corroborated these findings in a multi-institutional registry involving 282 patients [62].…”
Section: Open Versus Minimally Invasive Resectionmentioning
confidence: 65%
“…Another relevant study to contrast our findings would be the article by Kim et al [ 29 ] who compared minimally invasive and open pancreatectomy for nonfunctioning pancreatic neuroendocrine tumors (NF-PNET). In the case of patients with a proximal location lesion, there was no significant difference in the average rates of postoperative complications.…”
Section: Reviewmentioning
confidence: 98%